2020
DOI: 10.1093/europace/euaa094
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with cardiac amyloidosis and implantable cardioverter-defibrillator

Abstract: Aims Cardiac amyloidosis (CA) is associated with increased mortality due to arrhythmias, heart failure, and electromechanical dissociation. However, the role of an implantable cardioverter-defibrillator (ICD) remains unclear. We conducted case-control study to assess survival in CA patients with and without a primary prevention ICD and compared outcomes to an age, sex, and device implant year-matched non-CA group with primary prevention ICD. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Furthermore, 2 of the studies compared survival in CA patients with an inserted ICD vs a control population following ICD insertion. Compared with the control population, patients with CA have significantly reduced survival ( 49 , 50 ). Interestingly, the largest study found 1-year mortality for patients with CA and an ICD to be 26.9% vs 11.3% for nonischemic cardiomyopathy control patients ( 49 ).…”
Section: Ventricular Arrhythmiasmentioning
confidence: 98%
“…Furthermore, 2 of the studies compared survival in CA patients with an inserted ICD vs a control population following ICD insertion. Compared with the control population, patients with CA have significantly reduced survival ( 49 , 50 ). Interestingly, the largest study found 1-year mortality for patients with CA and an ICD to be 26.9% vs 11.3% for nonischemic cardiomyopathy control patients ( 49 ).…”
Section: Ventricular Arrhythmiasmentioning
confidence: 98%
“…Sudden cardiac death in ATTR-CA is thought to be uncommon, especially compared with AL-CA, but prospective studies are lacking. Although a number of studies (including both AL- and ATTR-CA) have shown appropriate implantable cardioverter-defibrillator (ICD) use in CA patients, none have shown greater survival compared with CA patients without ICDs ( 26 , 41 , 42 , 43 , 44 , 45 ). The incidence of appropriate ICD use varied from 6% to 32%, although the duration of follow-up and composition of the cohort in each study was heterogeneous ( 26 ).…”
Section: Management Of Arrhythmias Associated With Attr-camentioning
confidence: 99%
“…The 2017 American Heart Association/American College of Cardiology/Heart Rhythm Society guidelines recommend individualized decision making for both primary and secondary prevention with ICDs in CA ( 47 ). Despite incremental data on ICDs in CA since publication of these guidelines ( 41 , 45 ), the benefit of ICDs in ATTR-CA remains unclear.…”
Section: Management Of Arrhythmias Associated With Attr-camentioning
confidence: 99%
“…Kristen et al indicated low efficacy of ICD therapy and emphasized the frequent occurrence of electromechanical dissociation in CA patients [ 27 ]. On the contrary, several of the analyzed studies reported frequent and successful ICD therapy, but none of these have demonstrated a survival benefit [ 14 , 28 , 29 , 30 , 31 , 32 , 33 ].These discrepancies are due to multiple limitations of these studies. First, all of the studies included in this review were retrospective with various sample sizes (3–472 patients).…”
Section: The Role Of Icd Therapymentioning
confidence: 99%